Left bundle branch blocks do not predict mortality in oldest-old patients hospitalized for COVID-19: The GERIA-COVID cohort study. (March 2023) - Bannier, Adeline; Goldberg, Joëlle; Otekpo, Marie; Loison, Jocelyne; Gautier, Jennifer; Annweiler, Cédric; ,
Highlights: Cardiovascular comorbidities are recognized risk factors for COVID-19 severity. We found that left bundle branch blocks were not associated with 28-day and 3-month mortality in oldest-old patients hospitalized for COVID-19. Intraventricular conduction disorders are unlikely to explain COVID-19 severity in oldest-old adults. Abstract: This cohort study aimed to determine whether left bundle branch blocks (LBBB) in COVID-19 were associated with 28-day and 3-month mortality in oldest-old patients. LBBB were sought on electrocardiogram on hospital admission in patients aged 80 years or more admitted for COVID-19 to the geriatric acute care unit of Angers University Hospital, France, during the first wave of the pandemic. Eighty-five participants were included (mean ± SD, 88.3 ± 5.3 years; 48.2 % women; 14.1 % with LBBB; 18.8 % mortality after 28 days and 28.2 % after 3 months). LBBB was associated neither with 28-day (HR = 1.65, P  = 0.58) nor with 3-month (HR = 1.08, P  = 0.92) mortality, in fully-adjusted Cox regression.